DAMPAK ADOPSI IFRS TERHADAP PANJANG LAPORAN KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Cintantya Wasistha Patralalita; Agung Juliarto (Diponegoro Journal of Accounting, 2014)
This study conducted based on concerns from users of financial statements, there is too much information contained in the financial statements of IFRS. This study is conducted in order to examine the impact of IFRS adoption on the information load in the financial statements of public companies listed on the IDX, by measuring the length of financial statements. Measurement of the length of financial statements is conducted by dividing the financial statements into three sections, which include (1) major statements, (2) accounting policies, and (3) notes to the financial statements. This study also examine the difference between the change in length of complete financial statements of early adopters and late adopters of IFRS.Population of this study was non-financial companies listed on the IDX on 2010 and 2012. The sample was selected by purposive sampling method. Fifthy firms was used for analysis by using parametric t test.Results of this study show that the adoption of IFRS on public companies in Indonesia have an impact on increasing the length of the financial statements, specially in the accounting policies and notes to the financial statements section. These sections have significant additional amount of disclosure requirement such as financial instrument disclosures. Furthermore, finding indicates that change in length of the financial statements of late adopters is larger than early adopters.